The Effect of Intellectual Capital towards Firm Performance and Risk with Board Diversity as a Moderating Variable: Study in ASEAN Banking Firms - Innayah, Maulida Nurul; Pratama, Bima Cinintya; Hanafi, Mamduh Mahmadah (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2020)
This paper finds out the impact of intellectual capital on firm performance and risk. Moreover, this paper also examines whether the board diversity in terms of gender and nationality can strengthen the effect of intellectual capital towards firm performance and risk that operates in banking industries in ASEAN. The data in this study obtained from Bloomberg and OSIRIS database and also the firm’s annual reports over the period of 2012-2016 (375 observations) and conducted in ASEAN countries, namely Indonesia, Philippines, Malaysia, Singapore, and Thailand. The results find that the efficient and effective use of intellectual capital will make the firms achieved higher performance. Meanwhile, intellectual capital can help reduce credit risk. In the interaction effect, the result is consistent with social psychology theory and shows that the presence of board diversity actually reduces firm performance and increases risk.